FAKTOR-FAKTOR PENYEBAB STUNTING OBESITAS: NARRATIVE LITERATURE REVIEW - Prastiwi, Ratih Sakti; Qudriani, Meyliya; Umriaty; Nisa, Juhrotun (WOMB Midwifery Journal, 2023)
The problem of concurrent stunting and overweight (COS) in children has a low prevalence and is often overlooked. Children with COS are at increased risk for stunted growth and development and non-communicable diseases. Therefore, a preliminary review was conducted to identify the causes of COS in children under five years of age. A narrative review of the literature was conducted by searching the Scopus database using the keywords "concurrent stunting and overweight", "stunting and obesity", and "double burden of malnutrition", and 6 relevant articles were identified. Several important themes emerged from the literature review, namely maternal conditions during pregnancy and lactation, child feeding practices, completeness of immunization status, and household conditions and socio-demographics